Physical activity levels and sleep disturbances in Indonesian primary school students during the COVID-19 pandemic - Gunawan, Talitha Dinda; Sekartini, Rini (Indonesian Pediatric Society, 2024)
Background During the coronavirus disease-2019 (COVID-19) pandemic, the Indonesian government implemented a large-scale, social restriction policy, including the closure of schools and recreational facilities, which potentially altered children’s physical activity and sleep patterns. Objective To analyze for a possible association between physical activity levels and sleep disturbances in Indonesian primary school students during the COVID-19 pandemic. Methods This cross-sectional study was conducted on 437 children aged 7-13 years using data collected online in April-August 2020, including children’s sociodemographic characteristics, physical activity levels, and sleep patterns. The translated Indonesian version of Physical Activity Questionnaire for Children (PAQ-C) and the Children Sleep Habits Questionnaire-Abbreviated (CSHQ-A) were used to collect data. The data analyzed consisted of sociodemographic factors and physical activity levels, sociodemographic factors and sleep disturbances, and physical activity levels and sleep disturbances. Results Most children were physically inactive (60.87%) and experienced sleep disturbances (73.23%) during the COVID-19 pandemic. Female sex and physical inactivity were significantly associated. Male sex and sleep disturbances were significantly associated. Age 7 as the lowest age group was significantly associated with sleep disturbances. There was no significant association (P=0.248) between physical activity levels and sleep disturbances. Conclusion Most Indonesian primary school students were physically inactive and had sleep disorders during the COVID-19 pandemic. Female sex and physical inactivity were significantly associated, while male sex and sleep disturbances were significantly associated, age 7 (lower age group) and sleep disturbances were significantly associated. There was no significant association between physical activity levels and sleep disturbances in Indonesian primary school students during the COVID-19 pandemic.